EVALUASI ROTASI KERJA KARYAWAN: STUDI KEADILAN DISTRIBUTIF DAN PROSEDURAL ROTASI KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA - Heru Kurnianto Tjahjono; Diana Puspita Sari (Jurnal Riset Manajemen dan Bisnis, 2017)
The purpose of this study is to examine and analyze the effect of rotation of employees fairness aspecton satisfaction and employees performance in one of the private companies in Yogyakarta.Specifically, this research examines and analyzes the influence of distributive fairness and proceduralfairness employees rotation on employees job satisfaction and employees performance . This studyused survey method by using a census of all employees 90 people . Data analysis using SEM withAMOS program. The results show that the distributive justice rotation has positive effect on employeesatisfaction and employee performance . Procedural fairness rotation positive effect on employees jobsatisfaction, but has no direct effect on performance. Job satisfaction in this study mediate the effectof procedural fairness rotation of employees on employees performance.Keywords: Job rotation, distributive fairness, procedural fairness, employees satisfaction andperformance.